The case for the complete decriminalisation of abortion care in Nepal and beyond - Sabrina Germain; Mara Malagodi; Roshani Regmi; Radhika Saxena; Shivani Shinde (The Lancet Regional Health - Southeast Asia)
Summary: Our Viewpoint makes the case for the complete decriminalisation of abortion in Nepal (and beyond) as a key strategy to removing barriers to abortion care. The criminal framing of abortion—even if subject to exceptions—creates legal barriers to accessing abortion, which then compound socio-cultural and medical barriers. Nepal represents fertile ground for abortion law reform centred on complete decriminalisation due to its pioneering constitutional approach to sexual and reproductive health rights. However, even in Nepal's liberal context, the enduring partial criminalisation of abortion hinders abortion access, especially for historically marginalised groups and in remote areas. This Viewpoint recommends complete decriminalisation in Nepal and South and Southeast Asian countries facing similar socio-legal barriers to abortion access. Our position as legal experts echoes calls for the complete decriminalisation of abortion by national and international medical professional bodies, which we hope will inform regional strategies to improve access to safe abortions.